Relationship between parent-adolescent discrepancies in educational expectations and academic burnout: A response surface analysis - Xuanye Bai; Youzhi Song; Minlian Liang; Jia Peng; Tingting Ruan; Heping Xie (Acta Psychologica)
This study employed a questionnaire survey to collect multi-source data from 745 pairs of junior high school students and their parents, exploring the relationship between parent-adolescent discrepancies in educational expectations and students' academic burnout, characterized by boredom and fatigue due to disinterest or overwhelming workload. The primary focus was on the mediating effect of students' academic self-efficacy, which reflects an individual's confidence in their ability to manage academic tasks. To precisely address the matching and discrepancy in parent-adolescent educational expectations, as well as to quantify the mediating role of academic self-efficacy, polynomial regression and response surface analysis techniques were employed. Response surface analysis is a statistical technique specifically designed to examine how (mis)matching predictor variables relate to outcome variables, visualizing their relationship in three-dimensional space. The results showed that when parent-adolescent educational expectations were aligned, an increase in both levels could lead to decreased academic burnout through elevated academic self-efficacy. Conversely, when there was a discrepancy between parent and adolescent expectations, higher expectations from the child compared to the parent could further reduce academic burnout by enhancing academic self-efficacy. These results underscored the significant mediating effect of academic self-efficacy between parent-adolescent discrepancies in educational expectations and academic burnout. These findings provide a reference framework for parents and educators to develop targeted interventions and prevention strategies for adolescent academic burnout, focusing on harmonizing parental and adolescent educational expectations and enhancing academic self-efficacy.